Poor and Hunger: How Do Indigenous Peoples’ Respond to COVID-19 in Indonesia? - Niko, Nikodemus (Journal of Community Development Research (Humanities and Social Sciences); Vol 14 No 1 (2021): January - March 2021DO - 10.14456/jcdr-hs.2021.8, 2020)
Indigenous Dayaks in Balai District, Sanggau Regency West Kalimantan, Indonesia has a vulnerability and is at risk of Coronavirus exposure, especially for Dayaks aged 50 years and over. Since March, the COVID-19 outbreak was already a national disaster by the Indonesian National Disaster Management Agency. However, today, there is no specific operational guideline relevant to the COVID-19 response to indigenous people issued by national authorities. This means that guidelines for handling the health sector based on cultural approaches to indigenous people do not yet exist. This is an additional challenge for indigenous communities facing the Coronavirus outbreak (COVID-19). The research method uses qualitative. The data collection is an interview by phone and sourcing online. The data is also furnished with secondary data from various sources such as online news, proceedings and scientific journals, and books. Since the COVID-19 outbreak was discovered in Indonesia last March 2020, indigenous tribes in rural areas have not been urged to be prepared to deal with this virus. In the indigenous Dayak Benawan tribe, they were only alerted about the COVID-19 outbreak after this epidemic was a national disaster. Forms of public anticipation include spraying disinfectant liquid in every home and an appeal for handwashing with soap. Besides, the form of response of the local community is by carrying out the Nyapet ritual (warding off illness entering their village). This ritual requires that everyone stays at home for three days and three nights. They may not visit other people’s houses and may not receive guests. The Nyapet concept is the same as the local lockdown carried out by the Dayak Benawan community. Assistance from the government is only targeted at participating in social security participants and the Family of Hope Program or Program Kelurga Harapan . This means that government assistance is not comprehensive to the indigenous people of Dayak Benawan. On the other hand, some poor Dayak Benawan indigenous people are not registered as social security participants by the government. Keywords: Indigenous People, Dayak Benawan, Poor, Hunger, COVID-19